Effects of Yoga Respiratory Practice (Bhastrika pranayama) on Anxiety, Affect, and Brain Functional Connectivity and Activity: A Randomized Controlled Trial - Novaes, Morgana M.; Palhano-Fontes, Fernanda; Onias, Heloisa; Andrade, Katia C.; Lobão-Soares, Bruno; Arruda-Sanchez, Tiago; Kozasa, Elisa H.; Santaella, Danilo F.; de Araujo, Draulio Barros (Frontiers in Psychiatry, 2020)
Pranayama refers to a set of yoga breathing exercises. Recent evidence suggests that the practice of pranayama has positive effects on measures of clinical stress and anxiety. This study explored the impact of a Bhastrika pranayama training program on emotion processing, anxiety and affect. We used a randomized controlled trial design with thirty healthy young adults assessed at baseline and after 4 weeks of pranayama practices. Two functional MRI protocols were used both at baseline and post-intervention: an emotion task as well as a resting-state acquisition. Our results suggest that pranayama significantly decreased states of anxiety and negative affect. The practice of pranayama also modulated the activity of brain regions involved in emotional processing, particularly the amygdala, anterior cingulate, anterior insula, and prefrontal cortex. Resting-state fMRI showed significantly reduced functional connectivity involving the anterior insula and lateral portions of the prefrontal cortex. Correlation analysis revealed that changes in connectivity between the ventrolateral prefrontal cortex and the right anterior insula were associated with changes in anxiety. Although it should be noted that these analyses were preliminary and exploratory, it provides the first evidence that 4 weeks of Bhastrika pranayama significantly reduce the levels of anxiety and negative affect, and that these changes are associated with the modulation of activity and connectivity in brain areas involved in emotion processing, attention, and awareness. The study was registered at http://www.ensaiosclinicos.gov.br/rg/RBR-2gv5c2/ (RBR-2gv5c2).